2010
DOI: 10.1002/uog.7499
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of tricuspid atresia: intrauterine course and outcome

Abstract: Objective To evaluate the intrauterine course and outcome of tricuspid atresia detected in the fetus. Methods This was a retrospective review of all confirmed cases of tricuspid atresia detected prenatally between 1998 and 2006 in three tertiary referral centers in Germany. Results Fifty

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 20 publications
(32 reference statements)
0
20
0
4
Order By: Relevance
“…While in PSAIVS defect, the degree of RVH is determined by the size and type of the ventricular septal defect and is therefore predictable to some extent even in the intrauterine period [14][15][16][17][18][19][20][21][22][23], the likeliness of a univentricular (UV), or biventricular (BV) postnatal circulation in severe PSAIVS is much more difficult to predict. Postnatal series showed that RV size, TV size, and the coronary morphology are the most important determinants of UV or BV outcome [3,9,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…While in PSAIVS defect, the degree of RVH is determined by the size and type of the ventricular septal defect and is therefore predictable to some extent even in the intrauterine period [14][15][16][17][18][19][20][21][22][23], the likeliness of a univentricular (UV), or biventricular (BV) postnatal circulation in severe PSAIVS is much more difficult to predict. Postnatal series showed that RV size, TV size, and the coronary morphology are the most important determinants of UV or BV outcome [3,9,[24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…L'atrésie tricuspide est une anomalie isolée dans 75 à 80 % des cas [106,109]. Une ou plusieurs autres anomalies cardiovasculaires sont présentes chez 4 à 18 % des foetus [106,1075].…”
Section: Anomalies Associéesunclassified
“…Une ou plusieurs autres anomalies cardiovasculaires sont présentes chez 4 à 18 % des foetus [106,1075]. En dehors des anomalies aortiques ou pulmo naires évoquées ci-dessus, il s'agit essentiellement de la persistance d'une veine cave supérieure gauche, d'une crosse aortique droite, d'une juxtaposition des auricules ou d'un retour veineux pulmonaire anormal total [109]. Enfin, dans 10 à 15 % des cas coexistent des malformations extracardiaques importantes : association VACTERL, agénésie du ductus venosus, anomalies urogénitales, etc.…”
Section: Anomalies Associéesunclassified
See 2 more Smart Citations